Preparing a Composite Nanofiber Film Using Carbon Nanotubes and Polycaprolactone by Electrospinning Method - Çamlık, Gamze; Bilakaya, Besa; Keleş, Rümeysa; Degim, İsmail Tuncer (Trends in Pharmacy, 2024)
Background: Nanofibers produced from carbon nanotubes (CNT) have received greater attention in various scientific fields due to their unique properties. Electrospinning, a versatile and cost-effective nanofiber production technique, is a promising method for obtaining composite nanofibers by adding other components, such as carbon nanotubes. Methods: In this study, a 10% polycaprolactone (PCL) solution and a 0.1% CNTcontaining PCL solution were prepared. The prepared solutions were used to prepare nanofibers by changing various parameters (such as voltage, flow rate, and distance between the needle and the collector) in the electrospinning device. Then, the films were examined under an atomic force microscope and a Fourier transform infrared (FTIR) spectrophotometer to investigate their physical appearance and bonds in the structure of molecules. Surface topologies and properties of nanofibers were visualized under atomic force microscopy (AFM). Thus, the feasibility of a film layer preparation containing 0.1% CNT was tested. The technique is explained in detail and will be available for future drug adsorption/desorption studies to develop a drug delivery system. Results: The feed rate was increased due to the increase in viscosity in the electrospinning of carbon nanotube-doped nanofibers. As a result of half an hour of electrospinning, a 20 μm thick nanofiber surface was obtained. The absence of new peaks on FTIR and minimal shifts indicates minimal molecular interactions. A smooth surface was observed with AFM. The film was successfully prepared. Conclusion: This novel approach was the first study and successful preparation technique can easily adopted and used in future studies. Cite this article as: Çamlık, G, Bilakaya, B, Keleş, R, & Degim, İT. Preparing a composite nanofiber film using carbon nanotubes and polycaprolactone by electrospinning method. Trends Pharm, 2025, 2, 0020, doi: 10.5152/TrendsPharm.2025.24020.